HUBUNGAN KARAKTERISTIK PEKERJA DENGAN UNSAFE ACTION PADA TENAGA KERJA BONGKAR MUAT DI PT. TERMINAL PETIKEMAS SURABAYA - Pratama, Aditya Kurnia (Universitas Airlangga, 2015)
ABSTRACTUnsafe action is a trigger for work accident. Unsafe action happened for two reasons, such as unintentional mistakes and active errors or violation of a rule. Unsafe action influenced by the internal factor from workers itself, such as characteristic of workers. The objectivs of this research is to aims of this study are analyze the relationship between the characteristics of workers to unsafe action, in stevedor at PT. Terminal Petikemas Surabaya. This study was observational Descriptive. The sample was all stavedore in a group of which consisted of 60 people. The data presented in the form of distribution the frequency and tabulation cross then analyzed statistically the Spearman. The result of this study shownthat there was an relatively low association between the characteristic of workers with unsafe action, but there was one variable had the strong enough relationship, such as knowledge variable and unsafe action on stevedore in PT. Terminal Petikemas Surabaya with coefficient corelation 0.417. Based on the result of this study, suggestions that can be given to the HSE departement are scheduled refreshment through training and briefing to increase knowledge of occupational safety and health at work, meanwhile supervisor of field have to do a strict and firmly supervise to stevedore who performing unsafe action. So it expected to reduce the number of work accident in the process of loading and unloading.Keywords: Stevedore, unsafe action, characteristic of workers